The edge dislocation in a three-quarter plane. Part I: Influence functions - Churchman, C; Korsunsky, A; Hills, D (2006)
The problem of an edge dislocation, having arbitrary Burgers vector, and lying on one of the projection lines of a three-quarter plane is studied. The complete internal state of stress is found, with particular attention focused on the correct asymptotic behaviour. The solution is found in a form which makes it particularly suitable as the kernel of an integral equation formulation for an interface crack. © 2005 Elsevier SAS. All rights reserved.